UJI EFEKTIFITAS DEKOK BUNGA BELIMBING WULUH (Averrhoa bilimbi) SEBAGAI ANTIMIKROBA TERHADAP BAKTERI Salmonella Typhi SECARA IN VITRO - Ardananurdin, Alhamfaib; Winarsih, Sri; Widayat, Mahono (Fakultas Kedokteran Universitas Brawijaya, 2004)
Salmonella typhi is causative agent of typhoid fever and its still a main health problem in Indonesia.Pickle fruit flower had been recognized by Indonesian society that have usefulness to cure various diseases. Pickle fruit flower contain active substance of saponin, polifenol and flavonoids. The experimentallaboratoric aim was to know the efficacy of picklefruit flower decoct as an antimicrobial agent to Salmonella typhi in vitro byusing tube dilution method and continued by streaking on Bismuth Sulfite Agar. The concentration of pickle fruit flower decoct were 0%; 5%; 7.5%; 10%; 12.5%; and 15% and the sample of Salmonella typhi were 4 isolates derived from different patients. The concentration of Salmonella typhi was 104cell/ml. The result from the experiment was MIC at 10% and MBC at 12,5% concentration. The statistic analysis showed that pickle fruit flower decoct can reduce Salmonella typhi growth in vitro significantly (Anova, p=0.000) and there was a correlation between increasing concentration of pickle fruit flower with the reduced amount of colonies (correlation, R=-0.795). From this study we can conclude that pickle fruit flower decoct has an antimicrobial effect to Salmonella typhi fondly of MIC and MBC at 10% and 12.5% respectively. Key word:The pickle fruit flower, Salmonella typhi, MinimalInhibition Concentration (MIC), Minimal Bactericidal Concentration (MBC).